Basal Testosterone and Sex Hormone Binding Globulin Levels in the Prediction of Stimulation Parameters and Cycle Outcome in Cycling Patients Undergoing in Vitro Fertilization - Özlem Moraloğlu; Şebnem Özyer; Rana Karayalçın; Gülnur Özakşit; Murat Özel; Esra Tonguç; Leyla Mollamahmutoğlu (Medical Network, 2010)
OBJECTIVE: Basal serum testosterone (T) and sex hormone binding globulin (SHBG) levels in regularly cycling patients who undergone in vitro fertilization (IVF) treatment and their relations with stimulation parameters and IVF outcomes. STUDY DESING: Two hundred patients seeking their first IVF treatment from June 2007 to January 2008 were evaluated prospectively. Patients aged 23-39 with regular menstrual cycles and with FSH levels less than 12 mIU/ml were included. Basal concentrations of FSH, LH, E2, PRL, TSH with T and SHBG were determined. Free androgen index (FAI) was calculated. IVF stimulation parameters, fertilization and clinical pregnancy rates were evaluated. RESULTS: History of smoking was significantly associated with an increase in T. T had significantly positive association with the number of oocytes retrieved and the number of embryos transferred. However, neither T nor SHBG predicted fertilization or clinical pregnancy rates. CONCLUSION: Basal serum T levels during IVF have a positive correlation with part of the stimulation parameters including number of oocytes retrieved and the number of oocytes transferred. However, neither T nor SHBG has any affect on fertilization or pregnancy rates.